PRODUK PERMEN SNACK BAR DAN KACANG SACHI SANGRAI DI KELOMPOK WANITA TANI (KWT) CERIA, DESA SUKASARI KAB. KEPAHIANG - Afrianti, Nanda; Fretica, Dhea Oktari; Akbar, Amin; Aryes, Begi; Moulina, Methatias Ayu; Suparti, Yulia (Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2023)
The benefits of sacha inchi bean plants have several benefits, one of which is that the leaves contain antioxidants and can be eaten as vegetables or processed into tea, fruit / nut seeds contain fatty acids and oil extracted seeds / nuts sacha inchi has various benefits both for cosmetics as skin moisturizers. So far, Indonesia's market demand for sacha inchi is very high.  However, the supply from local farmers is fairly minimal, the type of activity used is the face-to-face method carried out by students from group 5 consisting of agribusiness study programs. To support this activity, the details of the implementation methods carried out are: Presentation of counseling materials on the benefits of sachi beans for health and the prevention of satanting processed sachi bean products into high-protein snack bars Based on the results of the implementation of student community service (PMM), it can be concluded that 1 The community understands the theory of the basics of making